The utility of arterial blood gas parameters and chest radiography in predicting appropriate intubations in burn patients with suspected inhalation injury—A retrospective cohort study. Issue 8 (December 2021) - Chotalia, Minesh; Pirrone, Christine; Ali, Muzzammil; Mullhi, Randeep; Torlinska, Barbara; Mangham, Thomas; England, Kaye; Torlinski, Tomasz
Highlights: A high rate of inappropriate intubations occur in burn patients with suspected inhalation injury. In this cohort, a pH < 7.30 had an 80% sensitivity and specificity for predicting appropriate intubations. A PaO2 :FiO2 ratio of <40 had a 70% sensitivity and specificity for predicting appropriate intubations. Adding pH and P/F ratio to the ABA intubation criteria increased their sensitivity in detecting appropriate intubations. Abstract: Background: This study evaluates the utility of arterial blood gas (ABG) parameters and chest radiography in predicting intubation need in patients with burn injuries with suspected inhalation injury. Methods: Patients with suspected inhalation injury admitted to a single centre, Burn Intensive Care Unit, between April 4th 2016 and July 5th 2019, were included. Admission ABG parameters and chest radiograph opacification were compared with whether the patient received an appropriate intubation: defined as intubation for a duration of over 48 h. Area under the receiver operator characteristic curve was calculated (AUROC). Results: Eighty-nine patients were included. The majority (84%; n = 75) were intubated, of which 81% (n = 61) received appropriate intubations. pH had an AUROC of 0.88 and a pH of <7.30 had an 80% sensitivity and specificity for detecting appropriate intubation. P/F ratio had an AUROC of 0.81 and a P/F ratio of <40 had a 70% sensitivity and specificity for appropriate intubation. Chest radiograph opacification had poor utility in this regard (AUROC = 0.69). Adding pH and P/F ratio to the ABA criteria improved their sensitivity in detecting appropriate intubations (sensitivity: ABA + pH + P/F = 0.97 vs ABA = 0.86; p = 0.013), without altering their specificity. Conclusions: In patients suspected inhalation injury, pH and P/F ratio were good predictors for appropriate intubations. Incorporating the parameters into the ABA criteria improved their clinical utility.